Bioavailability, Biotransformation, and Excretion of the Covalent Bruton Tyrosine Kinase Inhibitor Acalabrutinib in Rats, Dogs, and Humans - Podoll, Terry; Pearson, Paul G.; Evarts, Jerry; Ingallinera, Tim; Bibikova, Elena; Sun, Hao; Gohdes, Mark; Cardinal, Kristen; Sanghvi, Mitesh; Slatter, J. Greg (Drug metabolism and disposition, 2019)
Acalabrutinib is a targeted, covalent inhibitor of Bruton tyrosine kinase (BTK) with a unique 2-butynamide warhead that has relatively lower reactivity than other marketed acrylamide covalent inhibitors. A human [14C] microtracer bioavailability study in healthy subjects revealed moderate intravenous clearance (39.4 l/h) and an absolute bioavailability of 25.3% ± 14.3% (n = 8). Absorption and elimination of acalabrutinib after a 100 mg [14C] microtracer acalabrutinib oral dose was rapid, with the maximum concentration reached in <1 hour and elimination half-life values of <2 hours. Low concentrations of radioactivity persisted longer in the blood cell fraction and a peripheral blood mononuclear cell subfraction (enriched in target BTK) relative to plasma. [14C]Acalabrutinib was metabolized to more than three dozen metabolites detectable by liquid chromatography–tandem mass spectrometry, with primary metabolism by CYP3A-mediated oxidation of the pyrrolidine ring, thiol conjugation of the butynamide warhead, and amide hydrolysis. A major active, circulating, pyrrolidine ring-opened metabolite, ACP-5862 (4-[8-amino-3-[4-(but-2-ynoylamino)butanoyl]imidazo[1,5-a]pyrazin-1-yl]-N-(2-pyridyl)benzamide), was produced by CYP3A oxidation.Novel enol thioethers from the 2-butynamide warhead arose from glutathione and/or cysteine Michael additions and were subject to hydrolysis to a β-ketoamide. Total radioactivity recovery was 95.7% ± 4.6% (n = 6), with 12.0% of dose in urine and 83.5% in feces. Excretion and metabolism characteristics were generally similar in rats and dogs. Acalabrutinib’s highly selective, covalent mechanism of action, coupled with rapid absorption and elimination, enables high and sustained BTK target occupancy after twice-daily administration.